A escola de portas abertas e olhos fechados: situações de permanência desqualificada - Andrade, Daiana Cristina de (2014)
The interest of this subject of this study arose as a result of contact with reality in some public schools, where I've been as a teacher, often permeated by processes that enable poor school performance, being the most obvious facet of marginalization that the route does allow that portion the public school complete primary education provided illiterate. This research was then aimed to investigate forms of school survival o~ subjects who have not mastered the process of reading and writing, which are therefore conclude or for completing elementary school (9th grade) without being literate. The initial hypothesis is that the lack of mastery of the school cultural capital, most1y expressed through reading and writing, has articulated the centrality game for that portion, other words, hypothesized that they acquired in primary socialization provisions as incorporated the game rules operated by the school, through your secondary socialization, the point they can not survive in view of the type of school success that is valued in school. Procedures throughout the study had the basics key concepts of Pierre Bourdieu, but had other collaborations for their analyzes. The research was in two municipalities in São Paulo and the São Paulo State, were selected four students who were enrolled in or completed elementary education in public schools, whose criterion for the choice was not to be literate. Strategies such school subjects for survival given the condition of illiterate interviews were conducted to capture the school careers, the meaning of his stay at the school as well as the consequences of this remain disqualified at school, inside and beyond. Also, some documents were located in schools of the subjects and conducted interviews with representatives of the management of these schools. The results were different ways of acting young possible to be understood by analysis of adverse relationships that delineate situations, allowing you to identify all despite the lack of command of what has been the central minimal expectations of the school, which were to be educated, the literacy, the fact that different forms of expression that causes exclusion, of knowledge, but not for, many others